2022
DOI: 10.21203/rs.3.rs-2290457/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary Fiber during Gestation Improves Lactational Feed Intake of Sows by Modulating Gut Microbiota

Abstract: Background The feed intake of sows during lactation is often lower than their needs. High-fiber feed is usually used during gestation to increase the voluntary feed intake of sows during lactation. However, the mechanism underlying the effect of bulky diets on the appetites of sows during lactation have not been fully clarified. The current study was conducted to determine whether a high-fiber diet during gestation improves lactational feed intake (LFI) of sows by modulating gut microbiota. Methods We select… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Elevated levels of dietary fiber significantly influenced the performance, well-being, and behavioral aspects of sows [9]. It was shown that incorporating a fiber-rich diet during pregnancy enhances the reproductive outcomes, growth performance of nursing piglets, nutrient absorption, and milk composition in lactating sows [10]. Furthermore, AH contains bioactive compounds, such as antioxidants and phenolic compounds, which have been associated with various health benefits, including improved immune function and oxidative stress reduction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of dietary fiber significantly influenced the performance, well-being, and behavioral aspects of sows [9]. It was shown that incorporating a fiber-rich diet during pregnancy enhances the reproductive outcomes, growth performance of nursing piglets, nutrient absorption, and milk composition in lactating sows [10]. Furthermore, AH contains bioactive compounds, such as antioxidants and phenolic compounds, which have been associated with various health benefits, including improved immune function and oxidative stress reduction [11].…”
Section: Introductionmentioning
confidence: 99%